2021
DOI: 10.1177/13623613211010014
|View full text |Cite
|
Sign up to set email alerts
|

‘No idea of time’: Parents report differences in autistic children’s behaviour relating to time in a mixed-methods study

Abstract: An emerging body of research suggests that temporal processing may be disrupted in autistic children, although little is known about behaviours relating to time in daily life. In the present study, 113 parents of autistic and 201 parents of neurotypical children (aged 7–12 years) completed the It’s About Time questionnaire and open-ended questions about their child’s behaviour relating to time. The questionnaire scores were lower in the autistic compared with the neurotypical group, suggesting that behaviours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Although a generalized timing impairment was originally theorized, a more specific characterization of any differences in timing in autism is valuable in advancing understanding of the specific cognitive mechanisms affected. Recent qualitative work suggests differences in behavior relating to time can cause issues in daily life for many autistic people (Poole et al, 2021; Vogel et al, 2019), so improving understanding of timing processes should help point toward the development of targeted support to ameliorate problems.…”
Section: Experimental Study Of Timingmentioning
confidence: 99%
“…Although a generalized timing impairment was originally theorized, a more specific characterization of any differences in timing in autism is valuable in advancing understanding of the specific cognitive mechanisms affected. Recent qualitative work suggests differences in behavior relating to time can cause issues in daily life for many autistic people (Poole et al, 2021; Vogel et al, 2019), so improving understanding of timing processes should help point toward the development of targeted support to ameliorate problems.…”
Section: Experimental Study Of Timingmentioning
confidence: 99%
“…Researchers are more likely to emphasize changes in social communication rather than in basic cognitive function for individuals with high autistic traits, such as time perception. Many everyday activities require us to organize our behaviors with respect to time [18], and time processing is also the basis of many advanced cognitive functions, such as attention, memory, emotion, and language. This is crucial for an individual's cognitive development [19].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reports of individuals with ASD, as well as reports from relatives or physicians who have frequent contact with them, suggest that they have changed their time perception in their daily lives [22]. Using a questionnaire and open-ended questions, Poole et al (2021) found that behaviors related to time can have a considerable impact on the daily lives of children with autism [18]. Vogel et al (2019) reported a distinct pattern of interrupted-time experience from qualitative data acquired from 26 adults with high-functioning ASD [23].…”
Section: Introductionmentioning
confidence: 99%
“…Autistic people, their caregivers and clinicians have reported that the perception and understanding of time are affected (see Boucher, 2001;Poole, Gowen, Poliakoff, & Jones, 2021). The 'temporal deficit hypothesis' (Allman & DeLeon, 2009;Allman & Falter, 2015;Allman, 2011) proposes that differential maturation of timing processes across childhood development in autism leads to impaired duration and relative timing perception.…”
Section: Introductionmentioning
confidence: 99%